Assessment of Water Quality Status in Gebeng Industrial Area, Pahang, Malaysia - Islam, Mir Sujaul; Hossain, Mohamed Amjed; Zularisam, A. W.; Edriyana, Abd Aziz; Sobahan, Md Abdus (Universiti Kebangsaan Malaysia, 2012)
The study was conducted to assess the spatial variation of surface water quality in the Gebeng Industrial area, Pahang, Malaysia. Water quality parameters were analysed across the Tunggak River and surrounding area to disclose the spatial variation of the river water quality. Water samples were collected monthly from the selected 10 sampling site in the study area. The physico-chemical parameters were analysed using APHA & HACH standard methods as well as the selected heavy metals were determined using ICP-MS (Inductively Coupled Plasma Mass Spectrometry). The SPSS statistical software was used for data analyses. The study revealed that, the non-point source pollutants were associated with runoff from construction sites of newly developed industrial areas and the point source contributing the major pollutants especially from industrial wastes. Low levels of dissolved oxygen (DO) and higher concentration of chemical oxygen demand (COD), biochemical oxygen demand (BOD), total suspended solids (TSS), ammoniacal nitrogen and selected heavy metals made the water unusable. According to Interim National Water Quality Standard (INWQS), the major part of the river specially the mid-region was categorized as class V (very highly polluted) while some part was found to be in class IV (highly polluted) and rest of class III (polluted) as well. Based on Malaysian Water Quality Index (DOE-WQI), the maximum stations except lower and uppermost were in class IV, and highly polluted.